Effectivity of Various Î²-Carotene Concentration on Quality of Frozen-Thawed Semen of Garut Rams - Rizal, M (ANIMAL PRODUCTION, 2005)
The purpose of this research was to evaluate the quality of frozen-thawed semen of Garut rams that cryopreserved with Tris extender containing the various Î²-carotene concentrations. Semen was collected from four mature Garut rams using artificial vagina once a week. Immediately after initial evaluation, semen was divided into four parts and diluted with Tris extender containing 5% glycerol + 0% (control), 0.001% (Kt0.001), 0.002% (Kt0.002), and 0.003% (Kt0.003) Î²-carotene, respectively. Semen was loaded in 0.25 ml mini straw with the concentration of 200 million motile sperm. Semen was equilibrated at 5ÂºC for three hours, then frozen and stored in liquid nitrogen container for 7 days. Quality of processed-semen including motility, live sperm, intact acrosomal cap (IAC), and intact plasma membrane (IPM) were evaluated after diluted, equilibrated, and thawed, respectively. Concentration of malondialdehide (MDA) semen after thawing were evaluated. Data were analyzed as completely randomized design with four treatments and nine replicates. Means values were compared by least significant difference test at 0.05 significant level. Results indicated that mean value of post thawing motility and live sperm for Kt0.002 (50.55% and 56.78%) were significantly higher (P<0.05) than Kt0.001 (46.11% and 52.89%), Kt0.003 (46.67% and 53.33%) and control (46.67% and 52.33%). Mean value of post thawing IAC and IPM for Kt0.002 (51.00% and 53.78%) were significantly higher (P<0.05) than control ( 47.11% and 48.44%), but not significantly different with Kt0.001 (49.00% and 50.00%), and Kt0.003 (48.89% and 49.67%). MDA concentration of frozen-thawed semen for Kt0.001 (3.37 mg/kg), Kt0.002 (3.80 mg/kg), and Kt0.003 (4.61 mg/kg) were significantly lower (P<0.05) than control (5.24 mg/kg). in conclusion, concentration of 0.002% Î²-carotene in Tris extender is the optimal dose in improving frozen semen quality of garut rams. (Animal Production 7(1): 6-13 (2005)Â Key Words : Î²-carotene, frozen-thawed semen, intact plasma membrane, MDA, Garut Rams